Advanced Imaging of the Axial Skeleton in Spondyloarthropathy: Techniques, Interpretation, and Utility - Lambert, Robert G.W.; Dhillon, Sukhvinder S.; Jaremko, Jacob L. (Seminars in Musculoskeletal Radiology, 2012)
The development of available treatments for spondyloarthritis increases the need for accurate diagnosis and objective monitoring of response to therapy. Advances in MRI technology are improving the effectiveness of imaging of the sacroiliac joints and spine in spondyloarthritis. We discuss best practice techniques for MR image acquisition and interpretation with a view to optimizing the diagnostic utility of MRI in spondyloarthritis.
Keywords: spondyloarthritis; MRI; sacroiliitis; protocol; diagnostic utility